Quest - Becker, Aaron, 1974- (Somerville, Massachusetts : Candlewick Press, 2014)
In the Caldecott Honor-winning Journey, much of Becker's energy was devoted to the story's exquisite backdrops. Now, in the second wordless book of his planned trilogy, the focus is on his characters. On a rainy day in a city park, the girl who starred in Journey and the boy introduced at the end take refuge by a doorway under a bridge. To their surprise, a king emerges from the door just long enough to pass the two a map before soldiers apprehend him. Returning to the magical Pallonezia, they find the walled city in flames, under siege. Becker includes wonderfully evocative set pieces - a submerged city, a Mayan temple - as the pair follows the map to collect chalk markers in all the colors of the rainbow to free the king and save the city.
Ages 4-8.
Keywords: Kings and rulers -- Juvenile fiction; Magic -- Juvenile fiction; Drawing -- Juvenile fiction; Maps -- Juvenile fiction; Parks -- Juvenile fiction; Stories without words; Kings, queens, rulers, etc. -- Fiction; Magic -- Fiction; Drawing -- Fiction; Maps -- Fiction; Parks -- Fiction; Stories without words; Picture books for children; Children's stories -- Pictorial works